Modeling and Analyzing Architectural Diversity of Open Platforms - Schwichtenberg, Bahar; Schwichtenberg, Simon; Küster, Jochen; Zimmermann, Olaf; Engels, Gregor (Advanced Information Systems Engineering)

Usage of Local Online Platforms in Retail: Insights from retailers' expectations expectations - Berendes, Carsten Ingo; zur Heiden, Philipp; Niemann, Marco; Hoffmeister, Benedikt; Becker, Jörg (Proceedings of the Twenty-Eighth European Conference on Information Systems (ECIS2020))

Increasing the sensitivity in the determination of material parameters by using arbitrary loads in ultrasonic transmission measurements - Dreiling, Dmitrij; Itner, Dominik Thor; Feldmann, Nadine; Gravenkamp, Hauke; Henning, Bernd

Dynamic Reliability Management for FPGA-Based Systems - Anwer, Jahanzeb; Meisner, Sebastian; Platzner, Marco (International Journal of Reconfigurable Computing)
Radiation tolerance in FPGAs is an important field of research particularly for reliable computation in electronics used in aerospace and satellite missions. The motivation behind this research is the degradation of reliability in FPGA hardware due to single-event effects caused by radiation particles. Redundancy is a commonly used technique to enhance the fault-tolerance capability of radiation-sensitive applications. However, redundancy comes with an overhead in terms of excessive area consumption, latency, and power dissipation. Moreover, the redundant circuit implementations vary in structure and resource usage with the redundancy insertion algorithms as well as number of used redundant stages. The radiation environment varies during the operation time span of the mission depending on the orbit and space weather conditions. Therefore, the overheads due to redundancy should also be optimized at run-time with respect to the current radiation level. In this paper, we propose a technique called Dynamic Reliability Management (DRM) that utilizes the radiation data, interprets it, selects a suitable redundancy level, and performs the run-time reconfiguration, thus varying the reliability levels of the target computation modules. DRM is composed of two parts. The design-time tool flow of DRM generates a library of various redundant implementations of the circuit with different magnitudes of performance factors. The run-time tool flow, while utilizing the radiation/error-rate data, selects a required redundancy level and reconfigures the computation module with the corresponding redundant implementation. Both parts of DRM have been verified by experimentation on various benchmarks. The most significant finding we have from this experimentation is that the performance can be scaled multiple times by using partial reconfiguration feature of DRM, e.g., 7.7 and 3.7 times better performance results obtained for our data sorter and matrix multiplier case studies compared with static reliability management techniques. Therefore, DRM allows for maintaining a suitable trade-off between computation reliability and performance overhead during run-time of an application.

Design Principles for Explainable Sales Win-Propensity Prediction Systems - Thiess, Tiemo; Müller, Oliver; Tonelli, Lorenzo (International Conference on Wirtschaftsinformatik)

Pareto Explorer: a global/local exploration tool for many-objective optimization problems - Schütze, Oliver; Cuate, Oliver; Martín, Adanay; Peitz, Sebastian; Dellnitz, Michael (Engineering Optimization)
Multi-objective optimization is an active field of research that has many applications. Owing to its success and because decision-making processes are becoming more and more complex, there is a recent trend for incorporating many objectives into such problems. The challenge with such problems, however, is that the dimensions of the solution sets—the so-called Pareto sets and fronts—grow with the number of objectives. It is thus no longer possible to compute or to approximate the entire solution set of a given problem that contains many (e.g. more than three) objectives. On the other hand, the computation of single solutions (e.g. via scalarization methods) leads to unsatisfying results in many cases, even if user preferences are incorporated. In this article, the Pareto Explorer tool is presented—a global/local exploration tool for the treatment of many-objective optimization problems (MaOPs). In the first step, a solution of the problem is computed via a global search algorithm that ideally already includes user preferences. In the second step, a local search along the Pareto set/front of the given MaOP is performed in user specified directions. For this, several continuation-like procedures are proposed that can incorporate preferences defined in decision, objective, or in weight space. The applicability and usefulness of Pareto Explorer is demonstrated on benchmark problems as well as on an application from industrial laundry design.

How well do SEM algorithms imitate EM algorithms? A non-asymptotic analysis for mixture models - Blömer, Johannes; Brauer, Sascha; Bujna, Kathrin; Kuntze, Daniel (Advances in Data Analysis and Classification)

The gambler’s and hot-hand fallacies: Empirical evidence from trading data - Pelster, Matthias (Economics Letters)

Integrating Management Science into the HPC Research Ecosystem - Schryen, Guido (Communications of the ACM)

Second harmonic imaging of plasmonic Pancharatnam-Berry phase metasurfaces coupled to monolayers of WS2 - Spreyer, Florian; Zhao, Ruizhe; Huang, Lingling; Zentgraf, Thomas (Nanophotonics)
The nonlinear processes of frequency conversion such as second harmonic generation (SHG) usually obey certain selection rules, resulting from the preservation of different kinds of physical quantities, e.g. the angular momentum. For the SHG created by a monolayer of transition-metal dichalcogenides (TMDCs) such as WS 2 , the valley-exciton locked selection rule predicts an SHG signal in the cross-polarization state. By combining plasmonic nanostructures with a monolayer of TMDC, a hybrid metasurface is realized, which affects this nonlinear process because of an additional polarization conversion process. Here, we observe that the plasmonic metasurface modifies the light-matter interaction with the TMDC, resulting in an SHG signal that is co-polarized with respect to the incident field, which is usually forbidden for the monolayers of TMDC. We fabricate such hybrid metasurfaces by placing plasmonic nanorods on top of a monolayer WS 2 and study the valley-exciton locked SHG emission from such system for different parameters, such as wavelength and polarization. Furthermore, we show the potential of the hybrid metasurface for tailoring nonlinear processes by adding additional phase information to the SHG signal using the Pancharatnam-Berry phase effect. This allows direct tailoring of the SHG emission to the far-field.